Narrativas alternativas de la violencia en Rosa Cuchillo y La sangre de la aurora - Díaz Atilano, Carmen Jhoana (2019)
The present study intends to analyze the alternative narrative forms with which two novels, Rosa Cuchillo (1997) and Blood of the dawn (2013), recreate the Armed Conflict of Peru. We will argue that both, as part of a personal poetics of their authors, use resources such as fragmentation, ellipsis and polyphony to account for the context of violence. In addition, in both texts, the feminineelement stands out as a narrator and as an empowered character.